Chapter 39 Ethnolects of Dutch - Muysken, Pieter (De Gruyter, 2013)
In this chapter I discuss the different ethnolects that exist in the Netherlandic-speaking language context. It is convenient, but not entirely accurate, to define these simply as ethnic varieties of Dutch, on a par with dialects and sociolects. This is also suggested in the title of this chapter, but it ignores the fact that other languages are involved as well, to a greater or lesser degree (cf. Muysken 2010).In section 1.1. I present an encyclopedic overview of a number of ethnolects in the Netherlandic domain, in 1.2. I discuss problems of definition and demarcation, and in1.3. some sociolinguistic issues. Section 2. is devoted to a case study of a single well-known ethnolect, Surinamese Dutch, and section 3. to a wider European and global perspective on ethnolects. In section 4. a particular research project is presented, the Roots of Ethnolects study, and in 5. some issues for further research are presented.